SURAT EDARAN SEBAGAI INSTRUMEN ADMINISTRASI NEGARA DI MASA PANDEMI COVID-19 - Sjarif, Fitriani Ahlan; Kastanya, Efraim Jordi (Jurnal Hukum & Pembangunan, 2021)
Since Indonesia entered a period of health emergencies caused by the outbreak ofthe Covid-19, the Indonesian government has attempted to develop various legal instruments to regulatethe behavior of the Indonesian people. One of the instruments used is a circular letter. This paper tries to examine the normative juridical use of circular letters as an instrument of state administration during this pandemic. In legislation science and administrative law theory,a circular letter is a piece of legislationthat should be used as an official note to warn and remind, notto regulate.In practice, there are several problematic Circular Letters which are used to regulate the public.